KONTRIBUSI AGEN PERUBAHAN BIROKRASI DALAM PELAKSANAAN REFORMASI BIROKRASI: STUDI KASUS DI BADAN PENGAWAS OBAT DAN MAKANAN TAHUN 2020 - Perdhana Ari Sudewo (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2021)
Bureaucratic reform is one of the Government of Republic Indonesia programs to overcome problems related to overlapping tasks and functions between government agencies, civil servant professionalism, integration of public services, also performance and budget accountability. In its implementation, bureaucratic agents of change are needed. However, contribution and roles of bureaucratic agents of change have not been evaluated with measurable indicators. Therefore, a research needs to evaluate the contribution and roles of bureaucratic agents of change in supporting BPOM’s bureaucratic reform programs. The research method conducted through a survey to get an overview of employee perceptions of the implementation of bureaucratic reform and organizational culture. This issue is program's target for bureaucratic agents of change at BPOM in 2020. The result of the research obtained show that BPOM bureaucratic agents of change descriptively or through inferential statistical tests with the paired t-test contributes significantly to bureaucratic reform and the implementation of organizational culture at BPOM. The results are expected to provide policy input in increasing the role and contribution of bureaucratic agents of change in supporting the implementation of bureaucratic reforms at BPOM and in Indonesia.